Enhancing the Effectiveness of Student Learning through New Technologies and Creative Approaches - Yorqinoy Baxrom-qizi Ulasheva (International Journal of Formal Education, 2025)
The integration of new technologies and creative approaches in education significantly enhances the effectiveness of student learning. This paper explores various methods, including the use of interactive educational tools, online learning platforms, gamification, and AI-driven teaching assistants, which contribute to increased student engagement and independent learning. Interactive teaching methods, such as group discussions, role-playing, and simulations, foster critical thinking and collaboration among students. Additionally, the role of technological literacy is emphasized, highlighting its impact on career development and global education trends. The findings suggest that modernizing curricula, incorporating digital tools, and continuous teacher training are essential for improving learning outcomes in the 21st century.